Perancangan Aplikasi Sistem Penggajian Karyawan Berbasis Web Terintegrasi Absensi Fingerprint - Novita, Ita; Septian, Fajar (Program Studi Teknik Informatika Universitas Pamulang, 2022)
Salary is the payment in the form of money received by an employee, the results of his contributions as an employee and his ideas to achieve the company's goals. At PT. Taishan Alkes Indonesia Management in the payroll sector is still implementing a manual / conventional way payroll system. This can lead to errors at the time of salary calculation. As a new company that is growing, PT. Taishan Alkes Indonesia needs a data processing application that can help in processing employee payroll data quickly, precisely, and accurately. The method used in this payroll system is the waterfall method, which is a structured framework (framework) that is arranged in a series in an effort to develop information systems (software). The creation of this application uses the CodeIgniter framework and also web programming using PHP.